BS EN 2267-011. Aerospace series. Cables, electrical, for general purpose. Operating temperatures between -55 °C and 260 °C. Part 011. DZA family, single and multicore assembly for use in low pressure atmosphere .Product standard (16th June 2022) - British Standards Institution,
No abstract available